School of English for Business Administration - S. N. Ledenyova (Vestnik MGIMO-Universiteta)
Department of English Language № 4 was established in 1975 in order to work with students of the Faculty of International Economic Relations, Faculty of International Business and Business Administration and part-time students. Since 2001, the Department works exclusively with the students of the faculty of International Business Administration. Svetlana Ledenyova, PhD in Philology, Honored Worker of Higher Education of the Russian Federation is the Head of the Department, Effective teaching of English is achieved by inspired members of the department, specializing in linguistic and economic education. Most of them have received their education at leading universities in the UK and the USA. Over the past few years the Department published eight textbooks and other learning materials